First Report of Fusarium commune Associated with a Root Rot of Grapevine in China - Zhang, Jiao; Zhou, Yueyan; Li, Xinghong; Zhang, Wei; Li, Yonghua; Wang, Xiaodong; Yan, Jiye (Plant disease, 2023)
During last decade, species belonging to Fusarium, Rosellinia, Armillaria and Dactylonectria were confirmed as phytopathogens causing grapevine root diseases (Highet and Nair 1995; Teixeira et al. 1995; Calamit et al. 2021; Ye et al. 2021). From 2020 to 2021, grapevine decline was observed in several vineyards in Beijing region, China. Leaves turned yellow with brown necrotic patches and roots were poorly developed, which was suggesting that a root disease was affecting the vines. The disease incidence was up to 10-15% of the vineyard for sample collection. Symptomatic root samples (cv. 'Red Globe') were collected and tissue fragments were excised at the margin of the symptomatic tissue in order to isolate the potential pathogen. The surface was sterilized using 1.5% sodium hypochlorite for 3 min, followed by 70% ethanol for 30 sec, and rinsed three times with sterile distilled water (Ye et al. 2020). Tissues were dried and placed onto potato dextrose agar (PDA) plates, followed by incubation at 25°C under dark conditions for 3 d. Hyphal tips of fungi growing from the samples were transferred onto new PDA plates and incubated until they produced conidia. Next, single spores were transferred onto new PDA plates and incubated at 25°C for 7 d. Eight isolates numbered with JZB3110172 to JZB3110179 were obtained and their culture characters were identical, and the re-isolation percentage was 100%. Colonies were white to orange, with abundant fluffy aerial mycelium. Macroconidia were fusiform with a slightly curved apical cell and a foot-shaped basal cell, and measured 16.2-43.2 μm × 2.7-4.9 μm (n=50); microconidia were cylindrical, straight to slightly curved, 5.1-13 × 2.1-3.9 μm (n=50). Morphological characters of the isolates resembled to Fusarium commune (Skovgaard et al. 2003). For phylogenetic analysis, genomic DNA of the eight isolates was extracted with a DNA extraction kit (DNeasy plant Mini Kit). PCR amplifications of two phylogenetic markers (EF-1α and RPB2) were performed using the primers EF-1/EF-2 (Geiser et al. 2004) and RPB2-5F2/RPB2-7cR (Liu et al. 1995), respectively. The sequences were deposited in GenBank ON457645 to ON457660. Comparison of base pairs on Maximum likelihood (ML) phylogenetic analysis was conducted using the RAxML-HPC2 tool on XSEDE on the CIPRES Science Gateway platform (http://www.phylo.org/). The sequences of EF-1α and RPB2 of the eight isolates showed 99 to 100% similarity to the reference isolates of F. commune. In the phylogenetic tree, the isolates from this study clustered with the representative strains of F. commune (NRRL 52764, NRRL 28387 and NRRL 52744). Based on morphological characters and the phylogenetic results, all of isolates were identified as F. commune. Koch's postulates were conducted on healthy, 3-month-old grapevine 'Marselan'. Plant roots were trimmed with sterile scissors and then soaked in a spore suspension (1.0 × 106 spores mL-1) or sterile water (as the control) for 30 min. The inoculated grapevines were transplanted into pots and kept in the greenhouse at 25°C. After 14 days, all the inoculated plants developed necrosis and turned yellow. No symptoms were observed on the control. Koch's postulates were fulfilled by re-isolating the fungus from necrotic root tissues. The isolates obtained from the artificially infected tissue were identified again as F. commune based on morphological and molecular analyses. Overall, this is the first report of F. commune associated with a grapevine root rot globally, which lays a foundation for further study and developing disease control methods.